Effect of rocker-sole footwear on knee joint biomechanics while walking in people with ACL-reconstructed knees: a cross-sectional biomechanical study. Issue 4 (July 2020) - Bagheri, Azam; Saeedi, Hassan; Jalali, Maryam; Forghany, Saeed
Abstract : Background: Reinjury has occurred at a high rate after anterior cruciate ligament (ACL) reconstruction. Low knee flexion angles and high peak posterior ground reaction forces in landing tasks increase ACL loading. Some studies reported that rocker-sole shoes increased knee flexion angle in the early stance phase of the gait. The aim of this study was to investigate the biomechanics of walking with a custom-made heel-to-toe rocker shoe design, with special attention to the sagittal knee joint kinematics of patients after ACL reconstruction. Methods: This study examined 10 male participants with ACL-reconstruction participants. Three-dimensional gait analysis was performed under two conditions of level walking that were tested in random order using either modified footwear adapted with a heel-to-toe rocker sole or baseline footwear with a flat sole. The knee flexion angle at initial foot contact with the ground, average knee flexion angle from heel strike to 25% stance phase, and first peak knee flexion angle were compared across footwear conditions. Results: Walking with the heel-to-toe rocker shoes increased the knee flexion angle at the early stance phase of the gait cycle when compared with the baseline footwear. Conclusions: Rocker-shoe intervention was found to have potential as a rehabilitation tool to modify gait patterns in the sagittal plane of people with ACL-reconstructed knees and may protect against high reinjury rates. Further research is required to evaluate whether prolonged wear of rocker-sole shoes can modify lower extremity biomechanics of participants who have undergone ACL reconstruction. Level of Evidence: Level II.